2018
DOI: 10.1111/joca.12232
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Negative Social Cues in Tobacco Packaging: A Novel Approach to Discouraging Smokers

Abstract: Smoking is an international health crisis. Tobacco packaging is an important vehicle to convey antismoking messages, which to date have been predominantly limited to fear‐based health appeals. Using an experimental approach, we examine whether a novel alternative—using negative social cues on packaging—is effective at discouraging smoking. Our results support the notion that packaging which conveys to smokers that “others” view smoking negatively is sufficient to trigger feelings of self‐consciousness, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…belief that one is capable of evading the threatening outcome by engaging in effective compliant behaviors) as the underlying processes stimulating fear responses and motivated behavior (Orazi and Pizzetti, 2015; Pechmann et al , 2003; Rogers, 1975; Witte, 1992). We extend this work and propose a complementary mechanism that relies on self-appraisals, which aligns with recent research suggesting that inducing feelings of self-consciousness (Jeffrey and Thomson, 2019) helps elevate the motivational force of fear appeals. Specifically, our work highlights the importance of the assimilation process (i.e.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…belief that one is capable of evading the threatening outcome by engaging in effective compliant behaviors) as the underlying processes stimulating fear responses and motivated behavior (Orazi and Pizzetti, 2015; Pechmann et al , 2003; Rogers, 1975; Witte, 1992). We extend this work and propose a complementary mechanism that relies on self-appraisals, which aligns with recent research suggesting that inducing feelings of self-consciousness (Jeffrey and Thomson, 2019) helps elevate the motivational force of fear appeals. Specifically, our work highlights the importance of the assimilation process (i.e.…”
Section: Discussionsupporting
confidence: 84%
“…However, inconsistent findings suggest that additional message design elements need to be considered to get a more accurate depiction of the full extent to which fear appeals can stimulate behavior. Recent research has started to uncover additional design components, such as including an element of disgust (Morales et al , 2012) and incorporating social cues (Jeffrey and Thomson, 2019; Murdock and Rajagopal, 2017) to the communication, which enhance its persuasive power. Extending this line of work, we uncover a novel type of message design element that can influence consumers’ emotional response to the ad and motivated behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that negative emotional appeals, particularly over a long period of time, may become less effective, predictable, and even boring due to perceived negativity of these campaigns (Hastings et al, 2004). Negative appeals have been found to invoke self-protection and inaction rather than positive, active responses (Brennan and Binney, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is a practice that is becoming more stigmatized in recent years in several cultures. Achar et al (2022), Ferguson et al (2020, and Jeffrey and Thomson (2019) explore this practice by showing how smokers internalize and react to this changing context. Stigmatized sexual practices are explored by Achar et al (2022) and Veer and Golf-Papez (2018).…”
Section: Self-stigmamentioning
confidence: 99%